DEVELOPMENT OF A FLIPBOOK E-MODULE ON PROJECT-BASED PANCASILA INCORPORATING LOCAL WISDOM TO STRENGTHEN THE VALUES OF MUTUAL COOPERATION AND CREATIVITY IN KINDERGARTEN - Lidia Fransiska; Farida Mayar; Rakimahwati Rakimahwati; Delfi Eliza (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study aims to develop and evaluate the effectiveness of a local wisdom-based e-Module to enhance the dimensions of mutual cooperation (gotong royong) and creativity in early childhood education. The research uses a Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Conducted at Taman Kanak-Kanak Pembina Pancung Soal, the study involves children aged 4-6 years and teachers who will implement the e-Module. The analysis phase revealed that existing Pancasila-based modules were insufficient in fostering cooperative behavior among children. Consequently, a local wisdom-based e-Module, focusing on the use of Lokan shells as a creative learning material, was developed to support project-based learning that integrates the values of cooperation and creativity. The design phase involved planning the content, language, and visual design of the e-Module, which was then validated by experts, achieving an average validity score of 94%, indicating the module's high validity. The practicality test by teachers resulted in a 97% feasibility rating, while the effectiveness test with 15 participants showed a 94% effectiveness rate. Final evaluations indicated that the e-Module successfully enhanced cooperation and creativity in children while offering culturally relevant learning. This research provides important implications for the development of interactive learning media in early childhood education, utilizing digital technology and local wisdom to support character development and social skills in young learners.